STUDY ON SOCIOECONOMIC STATUS AND SOURCE OF WATER IN THOOTHUKUDI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
The primary sources of drinking water are groundwater and surface water, in this direct noted association between poor water quality and infectious diarrhoea. The present study was carried out both in rural and urban areas of Thoothukudi district A large proportion of the stored water in houses was found to be contaminated and therefore promotion of household water treatment and safe storage combined with hygienic practices would be very useful in preventing waterborne diseases. microbiologically contaminated which is a cause for concern as many diseases such as Diarrhoea, cholera, typhoid etc. are caused by contaminated water.